1973
DOI: 10.1017/s0003356100017049
|View full text |Cite
|
Sign up to set email alerts
|

The crude protein requirement of the early-weaned calf given urea, meat meal or soya bean meal with and without sulphur supplementation

Abstract: SUMMARYTwo experiments were conducted with 84 male British Friesian calves to estimate their nitrogen and sulphur requirements between 5 and 11 weeks of age. A basal 12 % crude protein (CP) diet was supplemented with meat meal, soya bean meal or urea to 15 or 18 % CP, and with sulphur to reduce the nitrogen to sulphur ratios of the diets to about 10 to 1.The weight gains and feed conversion ratios of the calves given the 12% CP diets were significantly poorer than those of the calves fed on the diets containin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
3

Year Published

1975
1975
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 24 publications
0
4
0
3
Order By: Relevance
“…Early work established the minimum CP concentration in starter diets to be around 16% (Leibholz & Kang, 1973;Morrill & Melton, 1973). Although many studies reported increased weight gains with diets containing more than 20% CP (Bartley, 1973;Schurman & Kesler, 1974;Akayezu et al, 1994), most researchers doubt the advantage of more than 220 g/kg CP in calf diets.…”
Section: Introductionmentioning
confidence: 99%
“…Early work established the minimum CP concentration in starter diets to be around 16% (Leibholz & Kang, 1973;Morrill & Melton, 1973). Although many studies reported increased weight gains with diets containing more than 20% CP (Bartley, 1973;Schurman & Kesler, 1974;Akayezu et al, 1994), most researchers doubt the advantage of more than 220 g/kg CP in calf diets.…”
Section: Introductionmentioning
confidence: 99%
“…Com exceção da produção fecal e da digestibilidade total do amido, nenhuma outra variável associada ao processo de digestão foi influenciada significativamente pelos tratamentos (P>0,10). Os resultados de digestibilidade ruminal e total dos componentes do alimento, obtidos no presente estudo, foram menores que os obtidos em outros estudos semelhantes, com terneiros consumindo dietas ricas em grãos (LEIBHOLZ & NAYLOR, 1971;LEIBHOLZ & KANG, 1973;SMITH et al, 1978;VEIRA et al, 1980), os quais geralmente são caracterizados por utilizarem níveis restritos de consumo de alimento. No presente estudo, o consumo de matéria seca foi relativamente alto (em média 2,6% do peso vivo) e as dietas continham altas proporções de grão de milho.…”
Section: Resultsunclassified
“…Em um estudo de digestão com terneiros recebendo dietas à base de cevada e suplementadas com farinha de carne e/ou uréia, LEIBHOLZ (1980) observou que a síntese de proteína microbiana em relação à matéria orgânica fermentada no rúmen foi similar entre os tratamentos, mas o fluxo e a absorção de aminoácidos no intestino delgado foram mais altos para as dietas contendo farinha de carne. Contudo, em estudos de desempenho de terneiros desmamados precocemente, quando uréia ou farinha de carne foram adicionadas para elevar de 12 para 18% o teor de proteína bruta da dieta basal, os resultados de consumo, ganho de peso e eficiência da utilização do alimento foram variáveis (LEIBHOLZ & NAYLOR, 1971;LEIBHOLZ & KANG, 1973;KOZLOSKI et al, 1996).…”
Section: Introductionunclassified
“…The calves were fed either whole milk or a commercial milk replacer once or twice daily, from birth to 5 weeks of age. From 5 weeks of age till the commencement of the experiment both calves were offered diets similar to those reported by Leibholz & Kang (1973). Danny was 25 weeks of age and Eric was 15 weeks of age at the commencement of the experimental period.…”
Section: Animalsmentioning
confidence: 95%